2013
DOI: 10.1016/j.diabres.2013.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Group follow-up compared to individual clinic visits after structured education for type 1 diabetes: A cluster randomised controlled trial

Abstract: Our data suggest that group follow-up as the sole means of follow-up after structured education for individuals with type 1 diabetes is as effective as a return to one-to-one clinic visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…It is noteworthy that another recent trial of the DAFNE intervention has also failed to show much improvement in HbA 1c levels. 85 We also assessed psychosocial outcomes, which reinforce the findings of other DAFNE studies 12,14,74,85 in demonstrating marked improvements across a range of measures at 6 months and maintenance at 12 months, with no differences between participants in the two different arms.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It is noteworthy that another recent trial of the DAFNE intervention has also failed to show much improvement in HbA 1c levels. 85 We also assessed psychosocial outcomes, which reinforce the findings of other DAFNE studies 12,14,74,85 in demonstrating marked improvements across a range of measures at 6 months and maintenance at 12 months, with no differences between participants in the two different arms.…”
Section: Discussionsupporting
confidence: 51%
“…Our findings also offer insights into what this continuing support should comprise. Despite growing interest in the use of group-based follow-up support to promote self-management of diabetes and other chronic conditions, our results, alongside those of others, 85,86 raise questions and concerns about promoting group-based support in routine clinical practice, particularly if this type of support is offered in isolation from other inputs and interventions. This is because a group-based approach may be incompatible with type 1 diabetes patients' need for individualised input from health professionals post course.…”
Section: Resultsmentioning
confidence: 64%
“…In the Irish DAFNE Study 10 , we showed improvements in (1) perceived burden of diabetes (measured by PAID) and (2) both the total quality of life and treatment satisfaction scores on the DSQOLS among a cohort of 437 DAFNE graduates, at 18 month follow up post participation in the DAFNE intervention. From baseline to 18 month follow up, PAID scores decreased on average by 9.13 percentage points, where lower scores indicated lower levels of distress (95% CI -10.63 to -7.64, p<0.001).…”
Section: Introductionmentioning
confidence: 90%
“…81 They carried out a large randomised trial of group follow-up compared with individual clinic visits for patients who had understands how to use it and is physically able to use the system and l agrees to use the system while having a structured education programme on diet and lifestyle, and counselling.…”
Section: Overview Of Evidence Base For Pump Therapymentioning
confidence: 99%